Empowering Smallholder Farmers in Zambia’s Climate Hotspots through Climate-Smart Innovations - Manoti, Dismas; Kakwasha, Keagan; Kikulwe, Enoch; Chinkwanda, George; Chinembiri, Evans (2024)
AICCRA Zambia has significantly empowered smallholder farmers in Eastern Province of Zambia by equipping them with validated climate-smart agricultural (CSA) practices and enhanced climate information services (CIS) to adapt to climate change. Field discussions with farmers revealed that those who adopted AICCRA’s climate-smart solutions such as drought-resistant seed varieties, conservation agriculture, agroforestry with Gliricidia, and agro-advisories on better planting timing achieved improved yields, even during challenging seasons. In Eastern Province, COMACO directly trained 175,000 farmers through its cooperative model, with 130,000 (50% women) adopting climate-smart agriculture practices. All farmers have access to enhanced climate information services through the climate-smart radio program, broadcast twice a week from 15:00 to 15:30 hours, with a repeat airing from 20:00 to 20:30 hours. The program receives calls from farmers, including those across the borders in Malawi and Mozambique. The success of this initiative underscores the importance of collaborative efforts in addressing climate challenges and improving livelihoods in vulnerable regions. Farmers have expressed appreciation for the timely and practical information provided, which has led to better planning and increased yields.